PENERAPAN KESELAMATAN KERJA PADA PROSES LOADING-UNLOADING CURRENT TRANSFORMER DI PT CPSI - Sulistyo, Arif Budi (Inaque : Journal of Industrial and Quality Engineering, 2023)
PT CPSI is engaged in the production of electrical equipment. One of the products are Current Transformers and Autoclaves. In production activities, when loading-unloading Current Transformers to and from the Autoclave, problems are encountered, such as cases of accidents that often occur and disturbing in the production process. Cause of accidents are lack of awareness of these employees that will have implications for the magnitude of the risk that must be borne by workforce and company. The purpose of this study is determining record of work accidents, hazards contained in the loading unloading area, risk assessment, risk control and risk control proposals at PT CPSI. This study uses the HIRADC method, histogram, Pareto diagram, and fishbone diagram. Based on observations, company data related to K3 and interviews with the directors of PT CPSI, obtained a history of work accidents, the risk matrix classification in 2020 obtained 1 case with extreme risk on work in the Autoclave, 2 cases high risk level, 2 cases for the moderate risk and 12 cases low risk were obtained. In 2021 there was increasing safety work experience which can be seen from decreasing rate of work accidents by 7 cases with low risk.